Chicago Man, K-T Man, and the Future of Behavioral Law and Economics - Prentice, Robert A. (2003)
Most law is aimed at shaping human behavior, encouraging that which is good for society and discouraging that which is bad.' Nonetheless, for most of the history of our legal system, laws were passed, cases were decided, and academics pontificated about the law based on nothing more than common sense assumptions about how people make decisions. A quarter century or more ago, the law and economics movement replaced these common sense assumptions with a well-considered and expressly stated assumption-that man is a rational maximizer of his expected utilities. Based on this premise, law and economics has dominated interdisciplinary thought in the legal academy for the past thirty years. In the past decade it has become clear, however, that people simply do not make decisions as modeled by traditional law and economics. A mountain of experiments performed in psychology and related disciplines, much of it in the heuristics and biases tradition founded by psychologists Daniel Kahneman and Amos Tversky, demonstrate that people tend to deviate systematically from rational norms when they make decisions